THE INVESTIGATION OF INFLUENCE OF GENETIC PROFILE ON THE EFFICACY AND SAFETY OF HALOPERIDOL IN PATIENTS WITH ALCOHOL DEPENDENCE - M. S. Zastrozhin; E. A. Grishina; D. A. Sychev; L. M. Savchenko; E. A. Bryun; M. V. Prudnikova; O. M. Saraeva; V. V. Trofimov (Архивъ внутренней медицины)
In case of patients with alcohol addiction haloperidol is used to control the exacerbation of the addiction, but the empirical dose selection of haloperidol often results in adverse side effects. Enzyme CYP2D6, which has encoded by gene CYP2D6 has high variability of activity, which depend from polymorphism of gene CYP2D6. P- glycoprotein, which has encoded by gene ABCB1 has high variability of activity, which depend from polymorphism of gene ABCB1. The study involved 20 men with alcohol addiction. The efficacy and safety of haloperidol was evaluated by international psychometric scales. The genotype of CYP2D6 was investigated by real-time PCR. The study revealed a statistically significant patterns between the polymorphism of CYP2D6 and the efficacy and safety of haloperidol. The genotype of ABCB1 was investigated by real-time PCR. The study revealed a statistically significant patterns between the polymorphism of ABCB1 and the efficacy and safety of haloperidol.